Phosphorus slag-based early-strength anti-crack concrete admixture and preparation method thereof

By chemically modifying the phosphorus slag and combining other materials, the problem of phosphorus slag being not effectively utilized is solved, the early strength performance, crack resistance and salt corrosion resistance of concrete are improved, and the resources of phosphorus slag are realized Chemical utilization and concrete performance improvement.

CN119430722AInactive Publication Date: 2025-02-14湖北津耀德新材料科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411804801.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, phosphorus slag has not been widely and reasonably used effectively, resulting in waste of resources and environmental pollution. At the same time, the preparation of high-performance concrete has high performance requirements for mineral blends, and existing blends are expensive and flowing. Poor sex problem.

Method used

Chemical modification of the phosphorus slag, including alkali treatment, hydrothermal method to generate TiO2, introduction of double bond groups and grafting reactions, improve the reactivity and dispersion of the phosphorus slag, and combine with fly ash and sodium-based bentonite. , diatomaceous earth, composite fibers and admixtures to optimize the internal structure of concrete.

Benefits of technology

The recycling and utilization of phosphorus slag has been achieved, the early strength, crack resistance and salt corrosion resistance of concrete have been improved, and the internal structure and mechanical properties of concrete have been optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005178927300000151
    Figure BDA0005178927300000151
Patent Text Reader

Abstract

The invention discloses a phosphorite slag-based early-strength anti-crack concrete admixture and a preparation method thereof, and the phosphorite slag-based early-strength anti-crack concrete admixture comprises the following raw materials by weight: 40-60 parts of modified phosphorite slag, 15-25 parts of fly ash, 7-10 parts of sodium bentonite, 5-8 parts of diatomite, 10-15 parts of an additive, and 15-25 parts of composite fiber. According to the admixture, phosphorus slag serves as a main raw material, the surface is modified through a chemical method, meanwhile, fly ash, sodium bentonite, kieselguhr, an additive and composite fibers are used as auxiliary materials, recycling of the phosphorus slag is achieved, the internal structure of concrete is optimized, and the early strength performance, the crack resistance and the salt corrosion resistance of the concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and particularly relates to a phosphate slag-based early-strength anti-cracking concrete admixture and a preparation method thereof. Background Art

[0002] Admixtures are inorganic mineral powders that replace part of the cement when preparing concrete and improve the performance of concrete. With the rapid development of my country's construction industry, there are higher requirements for the working performance, strength grade, and durability of concrete, and the demand for high-performance concrete is increasing. High-performance concrete is widely used in the construction industry for its excellent mechanical properties and durability. However, the preparation of high-performance concrete has higher requirements on the performance of various raw materials. At present, the mineral admixtures widely used in high-performance concrete mainly include ground slag powder, silica powder, and kaolin, but they have disadvantages such as high price and are not conducive to the fluidity of concrete, and have certain limitations in application.

[0003] With the rapid development of my country's economy and the rapid development of infrastructure, the generation of industrial solid waste is also accelerating. However, the resulting storage of industrial solid waste damages the soil and pollutes the environment. How to comprehensively utilize industrial solid waste, reduce emissions, and utilize it as resources has become a focus of social attention.

[0004] Phosphate slag, an industrial waste residue produced by the electric furnace process for producing yellow phosphorus, has not been widely and reasonably utilized for a long time. Most of it is piled up in the open air, which not only occupies a large amount of arable land, but also causes phosphorus and fluorine in it to gradually dissolve and seep into the ground after being washed by rainwater, polluting water sources, affecting plant growth, and seriously endangering human health. It is also a waste of resources. Phosphate slag is an acidic slag with calcium silicate as the main component and a certain activity. There has been relatively little research on the performance of phosphate slag, and there is currently no effective way to comprehensively utilize phosphate slag with high value.

[0005] In my country, the main application field of phosphate slag is building materials. At present, there are many studies on the application of phosphate slag in cement production, mainly focusing on the use of trace components such as fluorine and phosphorus contained in phosphate slag. These trace components can be used as mineralizers during the combustion of cement clinker. At the same time, phosphate slag can replace part of limestone and clay to provide CaO and SiO2 in cement clinker; the potential activity of phosphate slag can be used as a mixed material to produce phosphate slag cement and composite silicate cement. These two approaches have their own advantages and disadvantages. The former can improve the burnability of cement raw materials and increase the strength of clinker, but the slag consumption is small. Although the latter consumes a large amount of slag, the cement strength is also greatly reduced. In addition, phosphate slag is also used in the ceramic industry as a glaze to produce ceramic wall and floor tiles and glazed tiles; in the glass industry, it is used to melt decorative glass, etc.; it can also be used to produce silica bricks, etc.

[0006] Chinese patent CN110240434A discloses a titanium slag powder-phosphorus slag powder composite admixture and its preparation method and application method, which belongs to the field of building materials technology, and aims to provide a composite admixture that improves the early strength of concrete and reaches the tensile strength of C50 prestressed concrete continuous beams more quickly; reduces the viscosity of concrete mixtures and improves the workability of concrete mixtures. The main points of its technical solution are as follows: calculated by mass fraction, it includes the following components: 10-30 parts of slag powder, 10-30 parts of titanium-containing slag powder, 20-40 parts of phosphorus slag powder, 15-40 parts of silica fume, and 1-5 parts of activator; slag powder is water-quenched blast furnace slag powder; phosphorus slag powder is granulated electric furnace phosphorus slag powder. This invention is suitable for the batching of C50 beam concrete and has industrial value. However, none of the above patents process the slag powder. It is only added to the concrete in the form of raw material doping, which may affect the concrete's anti-carbonation and salt erosion resistance in the later stage. Summary of the invention

[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a phosphate slag-based early-strength and crack-resistant concrete admixture and a preparation method thereof. The admixture uses phosphate slag as the main raw material, and the surface is modified by chemical methods. It is supplemented with fly ash, sodium-based bentonite, diatomaceous earth, admixtures, and composite fibers. It not only realizes the recycling of phosphate slag, but also optimizes the internal structure of concrete, and improves the early strength performance, crack resistance and salt erosion resistance of concrete.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A phosphate slag-based early-strength anti-cracking concrete admixture, comprising the following raw materials in parts by weight:

[0010] 40-60 parts of modified phosphate slag, 15-25 parts of fly ash, 7-10 parts of sodium bentonite, 5-8 parts of diatomaceous earth, 10-15 parts of admixture, and 15-25 parts of composite fiber.

[0011] Preferably, a phosphate slag-based early strength and crack-resistant concrete admixture comprises the following raw materials in parts by weight:

[0012] 45-55 parts of modified phosphate slag, 15-25 parts of fly ash, 8-9 parts of sodium bentonite, 6-7 parts of diatomaceous earth, 12-14 parts of admixture, and 18-22 parts of composite fiber.

[0013] More preferably, a phosphate slag-based early strength and crack-resistant concrete admixture comprises the following raw materials in parts by weight:

[0014] 50 parts of modified phosphate slag, 20 parts of fly ash, 9 parts of sodium bentonite, 7 parts of diatomaceous earth, 13 parts of admixture, and 20 parts of composite fiber.

[0015] In the present invention, fly ash has a high specific surface area, and the active SiO2 therein has an extremely high volcanic ash effect, which can react with Ca(OH)2 crystals to generate CSH gel material, thereby reducing the porosity of the modified composite slag-cement paste interface layer, making the concrete structure denser and improving the interface adhesion.

[0016] Preferably, the method for preparing the modified phosphate slag comprises the following steps:

[0017] S1, adding phosphate slag into sodium hydroxide solution for impregnation treatment, filtering and drying after the treatment to obtain pretreated phosphate slag;

[0018] S2, adding the pretreated phosphate slag in step S1 into deionized water, then adding tetrabutyl titanate, stirring evenly, adding ammonia water, and performing a hydrothermal reaction. After the reaction is completed, filtering, washing, and drying to obtain a solid product;

[0019] S3, adding the solid product in step S2 to an ethanol aqueous solution, then adding vinyltrimethoxysilane, stirring to react, filtering, washing, and drying after the reaction is completed to obtain a phosphate slag containing double bonds;

[0020] S4, adding the double bond-containing phosphate slag in step S3 into dimethylformamide, and then adding allyl dimethyldithiocarbamate, 2-acrylamido-2-methyl-1-propanesulfonic acid, and ammonium persulfate to react at a constant temperature, and after the reaction is completed, filtering, washing, and drying to obtain modified phosphate slag.

[0021] Preferably, the concentration of sodium hydroxide in step S1 is 40-80 g / L, the temperature of the immersion treatment is 45-55° C., and the time is 2-3 h.

[0022] More preferably, the concentration of sodium hydroxide in step S1 is 50-70 g / L, the temperature of the immersion treatment is 50-55° C., and the time is 2-2.5 h.

[0023] In the present invention, the phosphate slag particles contain a small amount of phosphorus element. Since the bond energy of the phosphorus-oxygen bond and the silicon-oxygen bond is large, that is, the ionic bonding is strong, the chemical bond is not easy to break in the early stage of cement hydration and cannot quickly participate in the volcanic ash reaction. The breaking process of the chemical bond is accelerated by a strong alkaline substance.

[0024] Preferably, the mass concentration of the ammonia water in step S2 is 10-20%, the mass ratio of the pretreated phosphate slag, deionized water, tetrabutyl titanate, and ammonia water is 100:900-1200:50-60:80-100, the temperature of the hydrothermal reaction is 130-150°C, and the time is 6-10h.

[0025] More preferably, the mass concentration of the ammonia water in step S2 is 15-20%, the mass ratio of the pretreated phosphate slag, deionized water, tetrabutyl titanate, and ammonia water is 100:1000-1200:55-60:90-100, the temperature of the hydrothermal reaction is 130-140°C, and the time is 8-10h.

[0026] In the present invention, pretreated phosphate slag is subjected to a hydrothermal reaction with tetrabutyl titanate, so that TiO2 is generated in situ on the surface of the phosphate slag, the roughness of the surface of the phosphate slag is increased, and dense hydrates with a high degree of hydration are generated around the phosphate slag. The generated TiO2 can maximize the nucleation and filling effects during the hydration process, fill the pores or gaps between cement particles, and make the microstructure of the concrete denser.

[0027] Preferably, the volume concentration of ethanol in the ethanol aqueous solution in step S3 is 70-80%, the mass ratio of the solid product to vinyltrimethoxysilane is 100:15-20, the temperature of the stirring treatment is 60-70°C, and the time is 3-5h.

[0028] More preferably, the volume concentration of ethanol in the ethanol aqueous solution in step S3 is 75-80%, the mass ratio of the solid product to vinyltrimethoxysilane is 100:17-20, the temperature of the stirring treatment is 65-70°C, and the time is 3-4h.

[0029] In the present invention, the phosphate slag is modified by using vinyltrimethoxysilane to introduce double bond groups on its surface, thereby improving the dispersibility of the phosphate slag and facilitating the subsequent reactions.

[0030] Preferably, in step S4, the mass ratio of the double-bond-containing phosphate slag, allyl dimethyldithiocarbamate, 2-acrylamido-2-methyl-1-propane sulfonic acid, and ammonium persulfate is 100:15-25:10-15:1-2, and the isothermal reaction temperature is 85-95° C. and the reaction time is 2-3 h.

[0031] More preferably, in step S4, the mass ratio of the double-bond-containing phosphate slag, allyl dimethyldithiocarbamate, 2-acrylamido-2-methyl-1-propane sulfonic acid, and ammonium persulfate is 100:20-25:12-15:1.5-2, and the isothermal reaction temperature is 90-95° C. and the reaction time is 2-2.5 h.

[0032] In the present invention, allyl dimethyl dithiocarbamate and 2-acrylamido-2-methyl-1-propane sulfonic acid are introduced into phosphate slag through free radical reaction, and the introduced dithioamino and sulfonic acid groups have a great influence on Ca 2+It has good adsorption capacity, accelerates the hydration reaction of concrete, and thus improves the early strength of concrete.

[0033] Preferably, the preparation method of the composite fiber is as follows:

[0034] 50g of basalt fiber and 30-50g of polypropylene fiber are mixed evenly, and then an ethanol aqueous solution is added. After stirring, 10-15g of γ-aminopropyltriethoxysilane is added, and the mixture is reacted at 60-70°C for 3-4h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain pretreated mixed fibers. Subsequently, 80g of the pretreated mixed fibers are added to 800g of dimethylformamide, and then 10-15g of 3-(1-naphthyloxy)-1,2-propylene oxide and 30-40g of triethylamine are added. The mixture is reacted at 80-90°C for 2-4h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain the composite fibers.

[0035] In the present invention, basalt fiber is an inorganic continuous layered fiber made from natural basalt by high-temperature melting and drawing plate spinning. It has the characteristics of high strength, high elastic modulus, high temperature resistance, corrosion resistance, and small thermal expansion coefficient. It is an ideal cement reinforcing fiber. However, due to the smooth surface of basalt fiber, fewer active functional groups, and chemical inertness, this limits its application to a certain extent.

[0036] The polypropylene fiber and the basalt fiber are mixed evenly, and then the surface is modified with γ-aminopropyltriethoxysilane to introduce amino groups on the fiber surface and improve the surface activity of the fiber. The pretreated mixed fiber is then reacted with 3-(1-naphthyloxy)-1,2-propylene oxide. The epoxy group is opened and then reacted with the amino group to introduce naphthyl groups on the fiber surface. The naphthyl groups are hydrogen-bonded with the surface of cement particles to form a chemical adsorption layer, which not only reduces the adsorption force between cement particles, but also improves the bonding between the fiber and cement interface, thereby improving the density of the concrete and ensuring the crack resistance and durability of the concrete.

[0037] Preferably, the admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 15-25:10-15:8-12:5-9.

[0038] The present invention also protects a method for preparing the above-mentioned phosphate slag-based early-strength anti-cracking concrete admixture, comprising the following steps:

[0039] The modified phosphate slag, fly ash, sodium bentonite, diatomaceous earth, admixture and composite fiber are weighed in parts by weight, and stirred at 500-800 r / min for 20-30 min to obtain the composite slag-based concrete admixture.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) The phosphate slag-based early-strength anti-cracking concrete admixture provided by the present invention firstly treats the phosphate slag with alkali to etch the surface of the slag to improve the surface roughness and reaction activity, then uses a hydrothermal method to in-situ generate TiO2 on the surface of the phosphate slag to improve the surface roughness of the phosphate slag. Compared with physical blending, this method makes the TiO2 more uniformly dispersed; then, the phosphate slag is reacted with vinyl trimethoxy silane to introduce double bond groups on the slag surface through the action of silicon-oxygen bonds, and then the phosphate slag containing double bonds is reacted with allyl dimethyl dithiocarbamate, 2-propene The slag surface is grafted with allyl dimethyldithiocarbamate and 2-acrylamido-2-methyl-1-propane sulfonic acid by reacting with acrylamido-2-methyl-1-propane sulfonic acid. The sulfur atom in the dithioamino group can coordinate with the calcium ion in the slurry, so that Ca(OH)2 at the interface between the slag and the cement is preferentially nucleated, the hydration reaction of the cement matrix is ​​accelerated, and the early strength of the concrete is improved. At the same time, the dithioamino group and the sulfonic acid group are introduced into the surface of the phosphate slag by chemical bonding, which improves the bonding strength between the phosphate slag and the cement interface and improves the durability of the concrete.

[0042] (2) The phosphate slag-based early-strength crack-resistant concrete admixture provided by the present invention comprises composite fibers composed of basalt fibers and polypropylene fibers in a specific ratio. The low elastic modulus fibers and high elastic modulus fibers are mixed to achieve a multi-level synergistic effect, thereby better improving the interface performance of the fiber concrete and enabling the modified fibers to play a role in different stages of reinforcing the concrete and complement each other. The polypropylene fibers can limit the occurrence and growth of cracks, prevent microcracks from developing into macro cracks, and reduce chemical erosion of the concrete. The basalt fibers have high rigidity and can improve the flexural resistance of the concrete material. The composite fibers not only play the role of a single fiber but also produce a synergistic effect between the fibers, thereby improving the mechanical properties of the concrete. Furthermore, by surface modification of the composite fibers, the roughness of the fiber surface is increased, so that dense hydrates with a high degree of hydration are generated around the fibers, thereby improving the bonding performance of the composite fiber-concrete interface. Furthermore, the introduction of the naphthyl group not only improves the hydrophilicity and bonding properties of the composite fibers, but also improves the dispersibility of the composite fibers in concrete and improves the compactness of the composite fiber-matrix interface.

[0043] (3) The phosphate slag-based early-strength anti-cracking concrete admixture provided by the present invention uses modified phosphate slag and composite fiber as main raw materials, and is supplemented with fly ash, sodium-based bentonite, diatomaceous earth, glass microspheres, latex powder, glass microspheres, and aluminum sulfate. When added to concrete, it can improve the working performance of the concrete, optimize the internal structure of the concrete, and improve the density, mechanical properties, crack resistance and salt erosion resistance of the concrete, thereby realizing the recycling of phosphate slag. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The phosphate slag is produced in Guiyang, Guizhou Province, with a density of 2.88 g / cm 3 , chemical composition is shown in Table 1; the fly ash was purchased from Emeishan Taixin Environmental Protection Technology Co., Ltd., which is Class II fly ash with a particle size of 10-30 μm; the sodium-based bentonite was purchased from Anji Runxing New Materials Co., Ltd. with a mesh size of 325 meshes; the diatomaceous earth was purchased from Lingshou Yongshun Mineral Products Processing Plant with a mesh size of 325 meshes; the glass microbeads were purchased from Hebei Sanliujiu New Materials Technology Co., Ltd. with a mesh size of 300 meshes; the latex powder was purchased from Hebei Hongzheng Technology Co., Ltd.; the coal gangue was purchased from Lingshou Zhuoye Mineral Products Processing Plant with a mesh size of 325 meshes; the basalt fiber was purchased from Shandong Taicheng Fiber Co., Ltd. with a diameter of 17 μm and a length of 6 mm; the polypropylene fiber was purchased from Shandong Hongju Engineering Materials Co., Ltd. with a diameter of 10-25 μm and a length of 6 mm.

[0046] Table 1 Chemical composition (mass fraction %)

[0047] raw material <![CDATA[SiO2]]> <![CDATA[Fe2O3]]> <![CDATA[Al2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[SO3]]> <![CDATA[Na2O]]> <![CDATA[P2O5]]> loss Phosphate slag 37.21 0.23 3.37 44.92 3.64 0.62 0.07 0.26 2.48 -2.45

[0048] Example 1

[0049] A method for preparing a phosphate slag-based early-strength anti-cracking concrete admixture comprises the following steps:

[0050] 5 kg of modified phosphate slag, 12 kg of fly ash, 0.9 kg of sodium bentonite, 0.7 kg of diatomaceous earth, 1.3 kg of admixture, and 2 kg of composite fiber were weighed by weight, and stirred at 700 r / min for 25 min to obtain the composite slag-based concrete admixture.

[0051] The method for preparing the modified phosphate slag comprises the following steps:

[0052] S1, adding 1 kg of phosphate slag into a sodium hydroxide solution with a concentration of 60 g / L, immersing at 50° C. for 2.5 h, filtering and drying after the treatment, to obtain pretreated phosphate slag;

[0053] S2, adding 1 kg of the pretreated phosphate slag in step S1 to 11 kg of deionized water, then adding 0.55 g of tetrabutyl titanate, stirring evenly, adding 0.9 kg of 15% ammonia water, and hydrothermally reacting at 140° C. for 8 hours. After the reaction is completed, filtering, washing, and drying to obtain a solid product;

[0054] S3, adding 1 kg of the solid product in step S2 to 10 L of ethanol aqueous solution (the volume concentration of ethanol is 75%), then adding 180 g of vinyltrimethoxysilane, stirring and reacting at 65° C. for 4 h, filtering, washing and drying after the reaction is completed to obtain a phosphate slag containing double bonds;

[0055] S4, adding 1 kg of the phosphate slag containing double bonds in step S3 into 10 L of dimethylformamide, followed by adding 200 g of allyl dimethyldithiocarbamate, 130 g of 2-acrylamido-2-methyl-1-propanesulfonic acid, and 15 g of ammonium persulfate, and reacting at a constant temperature of 90° C. for 2.5 h. After the reaction is completed, filtering, washing, and drying are performed to obtain modified phosphate slag.

[0056] The preparation method of the composite fiber is as follows:

[0057] 50 g of basalt fiber and 40 g of polypropylene fiber were mixed evenly, and an ethanol aqueous solution was added. After stirring, 13 g of γ-aminopropyltriethoxysilane was added, and the mixture was reacted at 65° C. for 3.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain pretreated mixed fibers. Subsequently, 80 g of the pretreated mixed fibers were added to 800 g of dimethylformamide, and then 13 g of 3-(1-naphthyloxy)-1,2-propylene oxide and 35 g of triethylamine were added. The mixture was reacted at 85° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain the composite fibers.

[0058] The admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 20:13:10:7.

[0059] Example 2

[0060] A method for preparing a phosphate slag-based early-strength anti-cracking concrete admixture comprises the following steps:

[0061] 4 kg of modified phosphate slag, 1.5 kg of fly ash, 0.7 kg of sodium bentonite, 0.5 kg of diatomaceous earth, 1 kg of admixture, and 1.5 kg of composite fiber were weighed by weight, and stirred at 500 r / min for 30 min to obtain the composite slag-based concrete admixture.

[0062] The method for preparing the modified phosphate slag comprises the following steps:

[0063] S1, adding 1 kg of phosphate slag into a sodium hydroxide solution with a concentration of 40 g / L, immersing at 45° C. for 3 h, filtering and drying after the treatment, to obtain pretreated phosphate slag;

[0064] S2, adding 1 kg of the pretreated phosphate slag in step S1 to 9 kg of deionized water, then adding 0.5 kg of tetrabutyl titanate, stirring evenly, adding 0.8 kg of 20% ammonia water, and hydrothermally reacting at 130° C. for 10 hours. After the reaction is completed, filtering, washing, and drying to obtain a solid product;

[0065] S3, adding 1 kg of the solid product in step S2 to 10 L of ethanol aqueous solution (the volume concentration of ethanol is 70%), then adding 150 g of vinyltrimethoxysilane, stirring and reacting at 60° C. for 5 h, filtering, washing and drying after the reaction is completed to obtain a phosphate slag containing double bonds;

[0066] S4, adding 1 kg of the phosphate slag containing double bonds in step S3 into 10 L of dimethylformamide, followed by adding 150 g of allyl dimethyldithiocarbamate, 100 g of 2-acrylamido-2-methyl-1-propanesulfonic acid, and 10 g of ammonium persulfate, and reacting at 85 ° C for 3 h. After the reaction is completed, filtering, washing, and drying are performed to obtain modified phosphate slag.

[0067] The preparation method of the composite fiber is as follows:

[0068] 50 g of basalt fiber and 30 g of polypropylene fiber were mixed evenly, and an ethanol aqueous solution was added. After stirring, 10 g of γ-aminopropyltriethoxysilane was added, and the mixture was reacted at 60° C. for 4 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain pretreated mixed fibers. Subsequently, 80 g of the pretreated mixed fibers were added to 800 g of dimethylformamide, and then 10 g of 3-(1-naphthyloxy)-1,2-propylene oxide and 30 g of triethylamine were added. The mixture was reacted at 80° C. for 4 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain the composite fibers.

[0069] The admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 15:10:8:9.

[0070] Example 3

[0071] A method for preparing a phosphate slag-based early-strength anti-cracking concrete admixture comprises the following steps:

[0072] 6 kg of modified phosphate slag, 2.5 kg of fly ash, 1 kg of sodium bentonite, 0.8 kg of diatomaceous earth, 1.5 kg of admixture, and 2.5 kg of composite fiber were weighed by weight, and stirred at 800 r / min for 20 min to obtain the composite slag-based concrete admixture.

[0073] The method for preparing the modified phosphate slag comprises the following steps:

[0074] S1, adding 1 kg of phosphate slag into a sodium hydroxide solution with a concentration of 80 g / L, immersing at 55° C. for 2 h, filtering and drying after the treatment, to obtain pretreated phosphate slag;

[0075] S2, adding 1 kg of the pretreated phosphate slag in step S1 to 12 kg of deionized water, then adding 0.6 kg of tetrabutyl titanate, stirring evenly, adding 1 kg of 10% ammonia water, and hydrothermally reacting at 150° C. for 6 hours. After the reaction is completed, filtering, washing, and drying to obtain a solid product;

[0076] S3, adding 1 kg of the solid product in step S2 to 10 L of ethanol aqueous solution (the volume concentration of ethanol is 80%), then adding 200 g of vinyltrimethoxysilane, stirring and reacting at 70° C. for 3 h, filtering, washing and drying after the reaction is completed to obtain a phosphate slag containing double bonds;

[0077] S4, adding 1 kg of the phosphate slag containing double bonds in step S3 into 10 L of dimethylformamide, followed by adding 250 g of allyl dimethyldithiocarbamate, 150 g of 2-acrylamido-2-methyl-1-propanesulfonic acid, and 20 g of ammonium persulfate, and reacting at 95 ° C for 2 h. After the reaction is completed, filtering, washing, and drying to obtain modified phosphate slag.

[0078] The preparation method of the composite fiber is as follows:

[0079] 50 g of basalt fiber and 50 g of polypropylene fiber were mixed evenly, and then an ethanol aqueous solution was added. After stirring, 15 g of γ-aminopropyltriethoxysilane was added, and the mixture was reacted at 70° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain pretreated mixed fibers. Subsequently, 80 g of the pretreated mixed fibers were added to 800 g of dimethylformamide, and then 15 g of 3-(1-naphthyloxy)-1,2-propylene oxide and 40 g of triethylamine were added, and the mixture was reacted at 90° C. for 2 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain the composite fibers.

[0080] The admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 25:15:12:5.

[0081] Comparative Example 1

[0082] A method for preparing a phosphate slag-based early-strength anti-cracking concrete admixture comprises the following steps:

[0083] 5 kg of modified phosphate slag, 12 kg of fly ash, 0.9 kg of sodium bentonite, 0.7 kg of diatomaceous earth, 1.3 kg of admixture, and 2 kg of composite fiber were weighed by weight, and stirred at 700 r / min for 25 min to obtain the composite slag-based concrete admixture.

[0084] The method for preparing the modified phosphate slag comprises the following steps:

[0085] S1, adding 1 kg of phosphate slag into a sodium hydroxide solution with a concentration of 60 g / L, immersing at 50° C. for 2.5 h, filtering and drying after the treatment, to obtain pretreated phosphate slag;

[0086] S2. Add 1 kg of pretreated phosphate slag in step S1 into 10 L of ethanol aqueous solution (the volume concentration of ethanol is 75%), then add 180 g of vinyltrimethoxysilane, and stir the reaction at 65°C for 4 hours. After the reaction is completed, filter, wash and dry to obtain modified phosphate slag.

[0087] The preparation method of the composite fiber is as follows:

[0088] 50 g of basalt fiber and 40 g of polypropylene fiber were mixed evenly, and an ethanol aqueous solution was added. After stirring, 13 g of γ-aminopropyltriethoxysilane was added, and the mixture was reacted at 65° C. for 3.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain pretreated mixed fibers. Subsequently, 80 g of the pretreated mixed fibers were added to 800 g of dimethylformamide, and then 13 g of 3-(1-naphthyloxy)-1,2-propylene oxide and 35 g of triethylamine were added. The mixture was reacted at 85° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain the composite fibers.

[0089] The admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 20:13:10:7.

[0090] Comparative Example 2

[0091] A method for preparing a phosphate slag-based early-strength anti-cracking concrete admixture comprises the following steps:

[0092] 5 kg of modified phosphate slag, 12 kg of fly ash, 0.9 kg of sodium bentonite, 0.7 kg of diatomaceous earth, 1.3 kg of admixture, and 2 kg of composite fiber were weighed by weight, and stirred at 700 r / min for 25 min to obtain the composite slag-based concrete admixture.

[0093] The method for preparing the modified phosphate slag comprises the following steps:

[0094] S1, adding 1 kg of phosphate slag into a sodium hydroxide solution with a concentration of 60 g / L, immersing at 50° C. for 2.5 h, filtering and drying after the treatment, to obtain pretreated phosphate slag;

[0095] S2, adding 1 kg of the pretreated phosphate slag in step S1 to 11 kg of deionized water, then adding 0.55 g of tetrabutyl titanate, stirring evenly, adding 0.9 kg of 15% ammonia water, and hydrothermally reacting at 140° C. for 8 hours. After the reaction is completed, filtering, washing, and drying to obtain a solid product;

[0096] S3, adding 1 kg of the solid product in step S2 to 10 L of ethanol aqueous solution (the volume concentration of ethanol is 75%), then adding 180 g of vinyltrimethoxysilane, stirring and reacting at 65° C. for 4 h, filtering, washing and drying after the reaction is completed to obtain a phosphate slag containing double bonds;

[0097] S4, adding 1 kg of the phosphate slag containing double bonds in step S3 into 10 L of dimethylformamide, followed by adding 200 g of allyl dimethyldithiocarbamate, 130 g of 2-acrylamido-2-methyl-1-propanesulfonic acid, and 15 g of ammonium persulfate, and reacting at a constant temperature of 90° C. for 2.5 h. After the reaction is completed, filtering, washing, and drying are performed to obtain modified phosphate slag.

[0098] The preparation method of the composite fiber is as follows:

[0099] The composite fiber is obtained by uniformly mixing 50 g of basalt fiber and 40 g of polypropylene fiber.

[0100] The admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 20:13:10:7.

[0101] Comparative Example 3

[0102] A method for preparing a phosphate slag-based early-strength anti-cracking concrete admixture comprises the following steps:

[0103] 5 kg of modified phosphate slag, 12 kg of fly ash, 0.9 kg of sodium bentonite, 0.7 kg of diatomaceous earth, 1.3 kg of admixture, and 2 kg of composite fiber were weighed by weight, and stirred at 700 r / min for 25 min to obtain the composite slag-based concrete admixture.

[0104] The method for preparing the modified phosphate slag comprises the following steps:

[0105] S1, adding 1 kg of phosphate slag into a sodium hydroxide solution with a concentration of 60 g / L, immersing at 50° C. for 2.5 h, filtering and drying after the treatment, to obtain pretreated phosphate slag;

[0106] S2. Add 1 kg of pretreated phosphate slag in step S1 into 10 L of ethanol aqueous solution (the volume concentration of ethanol is 75%), then add 180 g of vinyltrimethoxysilane, and stir the reaction at 65°C for 4 hours. After the reaction is completed, filter, wash and dry to obtain modified phosphate slag.

[0107] The preparation method of the composite fiber is as follows:

[0108] The composite fiber is obtained by uniformly mixing 50 g of basalt fiber and 40 g of polypropylene fiber.

[0109] The admixture is a mixture of glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 20:13:10:7.

[0110] The admixtures prepared in Example 1-3 and Comparative Example 1-3 were applied to concrete. The cement used in the test was P.II 42.5 grade cement. The admixtures were the composite slag-based concrete admixtures prepared in Example 1-4 and Comparative Example 1-3. The coarse aggregate was natural crushed stone, which was 5-16 mm granite crushed stone with an apparent density of 2750 kg / m 3 ; Fine aggregate: machine-made sand, fineness modulus 2.4, apparent density 2758kg / m 3 ; The water reducing agent is polycarboxylic acid high-efficiency water reducing agent, and the water reducing rate is 30%; the water is tap water. The concrete ingredients are as shown in Table 2:

[0111] Table 2 Concrete mix ratio used in the test (%)

[0112] cement Admixture Coarse aggregate fine aggregate Water reducing agent water 11 4 41.5 36.5 0.7 6.3

[0113] The concrete prepared with the admixtures obtained in Examples 1-3 and Comparative Examples 1-3 was subjected to performance tests, and the compressive strength and flexural strength were determined with reference to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete"; the chloride ion diffusion coefficient and crack resistance were determined with reference to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and the specific data are shown in Table 3.

[0114] Table 3

[0115]

[0116] It can be seen from Table 3 above that the phosphate slag-based early-strength anti-cracking concrete admixture prepared by the present invention can improve the overall mechanical properties of concrete when used in concrete, and also has excellent anti-cracking ability and salt erosion resistance, and has good application prospects.

[0117] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A phosphate slag-based early strength and crack-resistant concrete admixture, characterized in that: By weight, it includes the following raw materials: 40-60 parts of modified phosphate slag, 15-25 parts of fly ash, 7-10 parts of sodium bentonite, 5-8 parts of diatomaceous earth, 10-15 parts of admixture, and 15-25 parts of composite fiber.

2. The phosphate slag-based early strength and crack-resistant concrete admixture according to claim 1, characterized in that: By weight, it includes the following raw materials: 45-55 parts of modified phosphate slag, 15-25 parts of fly ash, 8-9 parts of sodium bentonite, 6-7 parts of diatomaceous earth, 12-14 parts of admixture, and 18-22 parts of composite fiber.

3. The phosphate slag-based early strength and crack-resistant concrete admixture according to claim 1, characterized in that: The preparation method of the modified phosphate slag comprises the following steps: S1, adding phosphate slag into sodium hydroxide solution for impregnation treatment, filtering and drying after the treatment to obtain pretreated phosphate slag; S2, adding the pretreated phosphate slag in step S1 into deionized water, then adding tetrabutyl titanate, stirring evenly, adding ammonia water, and performing a hydrothermal reaction. After the reaction is completed, filtering, washing, and drying to obtain a solid product; S3, adding the solid product in step S2 to an ethanol aqueous solution, then adding vinyltrimethoxysilane, stirring to react, filtering, washing, and drying after the reaction is completed to obtain a phosphate slag containing double bonds; S4, adding the double bond-containing phosphate slag in step S3 into dimethylformamide, and then adding allyl dimethyldithiocarbamate, 2-acrylamido-2-methyl-1-propanesulfonic acid, and ammonium persulfate to react at a constant temperature, and after the reaction is completed, filtering, washing, and drying to obtain modified phosphate slag.

4. The phosphate slag-based early strength and crack-resistant concrete admixture according to claim 3, characterized in that: The concentration of sodium hydroxide in step S1 is 40-80 g / L, the temperature of the immersion treatment is 45-55° C., and the time is 2-3 h.

5. The phosphate slag-based early strength and crack-resistant concrete admixture according to claim 3, characterized in that: The mass concentration of the ammonia water in step S2 is 10-20%, the mass ratio of the pretreated phosphate slag, deionized water, tetrabutyl titanate, and ammonia water is 100:900-1200:50-60:80-100, the temperature of the hydrothermal reaction is 130-150° C., and the time is 6-10 hours.

6. The phosphate slag-based early-strength anti-cracking concrete admixture according to claim 3, characterized in that: In step S3, the volume concentration of ethanol in the ethanol aqueous solution is 70-80%, the mass ratio of the solid product to vinyltrimethoxysilane is 100:15-20, the temperature of the stirring treatment is 60-70° C., and the time is 3-5 hours.

7. The phosphate slag-based early strength and crack-resistant concrete admixture according to claim 3, characterized in that: In step S4, the mass ratio of the double-bond-containing phosphate slag, allyl dimethyldithiocarbamate, 2-acrylamido-2-methyl-1-propanesulfonic acid, and ammonium persulfate is 100:15-25:10-15:1-2, and the isothermal reaction temperature is 85-95° C. and the reaction time is 2-3 h.

8. The phosphate slag-based early-strength anti-cracking concrete admixture according to claim 1, characterized in that: The preparation method of the composite fiber is as follows: 50g of basalt fiber and 30-50g of polypropylene fiber are mixed evenly, and then an ethanol aqueous solution is added. After stirring, 10-15g of γ-aminopropyltriethoxysilane is added, and the mixture is reacted at 60-70°C for 3-4h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain pretreated mixed fibers. Subsequently, 80g of the pretreated mixed fibers are added to 800g of dimethylformamide, and then 10-15g of 3-(1-naphthyloxy)-1,2-propylene oxide and 30-40g of triethylamine are added. The mixture is reacted at 80-90°C for 2-4h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain the composite fibers.

9. The phosphate slag-based early-strength anti-cracking concrete admixture according to claim 1, characterized in that: The admixture is prepared by mixing glass microspheres, latex powder, coal gangue and aluminum sulfate in a mass ratio of 15-25:10-15:8-12:5-9.

10. A method for preparing the phosphate slag-based early strength and crack-resistant concrete admixture according to any one of claims 1 to 9, characterized in that: The following steps are involved: The modified phosphate slag, fly ash, sodium bentonite, diatomaceous earth, admixture and composite fiber are weighed in parts by weight, and stirred at 500-800 r / min for 20-30 min to obtain the composite slag-based concrete admixture.

Citation Information

Patent Citations

  • Titanium slag powder-phosphorus slag powder composite admixture, and preparation method and application method thereof

    CN110240434A